Passenger-centric factors influencing the experience of aircraft comfort. Issue 2 (4th March 2018) - Patel, Harshada; D'Cruz, Mirabelle
ABSTRACT: Enhancing passenger comfort in an air cabin environment is uniquely challenging. Air travel offers a restrictive passenger experience in terms of available space and the ability to change one's position or journey. The first step to designing experiences for comfort is to take a broader view of the factors which influence in-flight comfort. While many studies have considered the design and services of aircrafts and airlines, this review focuses on the passenger and the internal and external factors which can affect their comfort. We present a descriptive model of comfort that comprises factors such as individual characteristics, personal travel context and interaction with others. This model could be used to develop an improved aircraft passenger experience.